ROLE OF HERBS AS ANTHELMINTIC IN THE CONTROL OF PARASCARIASIS IN EQUINES - Zulfiqar Ali Beg; Nabila Roohi; Dr. Zahid Iqbal; Muhammad Amir Iqbal; Aayet Zulfiqar (Journal of Animal and Plant Sciences, 2023)
Parascariasis is the most common disease of horses, which needs strict control to prevent losses in the equine industry. The present study was conducted to evaluate the effectiveness of locally accessible herbal plants, as natural remedies, in managing Parascaris equorum infection relative to a most efficacious but expensive allopathic medicine Piperazine Adipate (PA). One hundred and ten horses naturally infected with Parascaris equorum were randomly allocated to five treatment groups each having ten animals. The treatments included aqueous extracts of three herbal drugs that is Nigella sativa (N. sativa) seeds, Fumaria parviflora (F. parviflora ) leave, Flemingia macrophylla (F. macrophylla) leaves, positive control with PA and untreated negative control. Plant extracts were administered through a nasogastric tube, on day 0 and 18 at a dose rate of 0.05, 0.1 and 0.15 g/kg body weight (BW) of horses. Piperazine adipate was given at a dose rate of 0.113 g/kg BW. All of the herbal extracts, at a dosage of 0.15 g/kg BW, showed increased efficacy as indicated by a significant (p<0.01) reduction in eggs per gram (EPG) of faecal samples on day 18 of the first treatment. Further reduction (p<0.01) in EPG was noticed on day 28 of the 2nd treatment. Efficacy was highest for N. sativa on the 28th-day post-treatment which was 86.08% as compared to 82.11% and 73.74% for F. parviflora and F. macrophylla, respectively. Piperazine adipate presented an efficacy of 85.94% and 100% on the 18th and 28th day of the trial, respectively. All of the herbal extracts were found to be potent anthelmintics, however, N. sativa proved to be most effective.
Keywords: Horse; Parascaris equorum; Nigella sativa; Fumaria parviflora; Flemingia macrophylla; Piperazine adipate